STAT-3 RNAscope Determination in Human Diffuse Large B-Cell Lymphoma() - Tamma, Roberto (Transl Oncol, 2019)
BACKGROUND: Diffuse large B-cell lymphoma (DLBCL) is the most common form of non-Hodgkin's lymphoma. Signal transducer and activator of transcription 3 (STAT3) is a cytoplasmic transcription with many important functions, including regulation of cell proliferation, differentiation, survival, angiogenesis, and immune response. MATERIALS AND METHODS: In this study, we have compared by means of RNAscope technology STAT3 RNA expression in human DLBCL in a selected group of activated B-cell–like DLBCL (ABC-DLBCL) patients with another group of germinal center B-cell–like DLBCL (GBC-DLBCL) patients. RESULTS: The results have shown that ABC DLBCL tissue samples contained a significantly higher number of STAT3-positive cells as compared with GCB tissue samples. Moreover, by means of confocal immunofluorescence analysis, we have observed that tumor vessels in ABC samples appeared lined by endothelial cells expressing both FVIII and STAT3 signals, while in GCB samples, only few vessels coexpressed FVIII and STAT3. CONCLUSIONS: These data confirm other reports showing that STAT3 is highly expressed and activated in ABC-DLBCL and our previously published data demonstrating that, in primary central nervous system lymphoma, tumor vessels appeared lined by endothelial cells expressing both FVIII and STAT3.